Kevin Fredy Hinterberger, Regularisations of Irregularly Staying Migrants in the EU. A comparative Legal Analysis of Austria, Germany and Spain - Vacas Fernández, Félix (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
Este artículo reseña: Kevin Fredy HINTERBERGER, Regularisations of Irregularly Staying Migrants in the EU.A comparative Legal Analysis of Austria, Germany and Spain, Hart Publishing/Nomos, Baden-Baden (Germany), 2023, 398 pp.
Keywords: European migratory Law; migrant regularization; comparative study